Surveillance for colonization, transmission, and infection with methicillin-susceptible staphylococcus aureus in a neonatal intensive care unit - Nurjadi, Dennis; Eichel, Vanessa; Tabatabai, Patrik; Klein, Sabrina; Last, Katharina; Mutters, Nico T.; Pöschl, Johannes; Zanger, Philipp; Heeg, Klaus; Boutin, Sébastien (JAMA network open, 2021)
Staphylococcus aureus is one of the leading causes of infections in neonatal intensive care units (NICUs). Most studies in this patient group focus on methicillin-resistant S aureus or the outbreak setting, whereas data for methicillin-susceptible S aureus are limited.To identify risk factors for S aureus colonization and infections in hospitalized newborns and to investigate S aureus transmission and its dynamics in a nonoutbreak setting.This monocentric cohort study in a tertiary NICU in Heidelberg, Germany, enrolled all hospitalized neonates (n = 590) with at least 1 nasal screening swab positive for S aureus. Data were collected from January 1, 2018, to December 31, 2019.Weekly screening for S aureus colonization was performed for all newborns until discharge.The primary end point was any S aureus infection until hospital discharge. Transmission of S aureus and performance of routine typing to detect transmissions were defined as the secondary outcomes of the study.In total, 590 newborns were enrolled (276 [46.8%] female and 314 [53.2%] male; 220 [37.3%] with birthweight <1500 g; 477 [80.8%] preterm; 449 [76.1%] singletons; 419 [71.5%] delivered via cesarean section). The median length of stay was 26 (range, 10-62) days. Overall, 135 infants (22.9%) were colonized by S aureus at some time during their hospital stay. The median time to first detection was 17 (interquartile range, 11-37) days. The overall incidence of S aureus infection was 1.7% (10 of 590). Low birth weight (<1500 g [odds ratio, 9.3; 95% CI, 5.9-14.6; P < .001]) and longer hospital stay (odds ratio, 2.3; 95% CI, 1.9-2.7; P < .001) were associated with colonization. Nasal carriage was significantly associated with S aureus infection (odds ratio, 8.2; 95% CI, 2.1-32.3; P = .002). A total of 123 of 135 colonization isolates were sequenced. All recoverable infection isolates (4 of 7) of newborns with colonization were genetically identical to the colonizing isolate. Whole-genome sequencing indicated 23 potential transmission clusters.The findings of this cohort study suggest that nasal colonization is a relevant risk factor for S aureus infection in a nonoutbreak NICU setting. In colonized newborns, infection and colonization isolates were genetically identical, suggesting that eradication of colonization may be a useful measure to prevent infection. Further investigations are necessary to validate and assess the generalizability of our findings.